Роль суду й прокуратури в забезпеченні законності правових актів органів виконавчої влади та органів місцевого самоврядування - Кравчук, Володимир Миколайович; Kravchuk, V. M. (Одеська національна юридична академія, 2008)
Робота є комплексним науковим дослідженням проблем судоустрою, судочинства і діяльності прокуратури із забезпечення законності актів місцевих органів виконавчої влади та місцевого самоврядування. У роботі розглянуто питання правової природи цих актів, особливостей актів органів виконавчої влади та органів місцевого самоврядування, забезпечення їх законності; наведено міркування щодо шляхів розвитку адміністративної юстиції в Україні і підвищення її ролі у здійсненні контролю за нормотворчою і правозастосувальною діяльністю владних структур; роль прокуратури у захисті прав і свобод шляхом здійснення нагляду за законністю актів органів виконавчої влади і органів місцевого самоврядування, представництва в суді інтересів громадян та юридичних осіб. Внесено пропозиції про зміни та доповнення до законів України «Про прокуратуру», «Про місцеві державні адміністрації», «Про місцеве самоврядування в Україні», «Про судоустрій України», КАС України, інших нормативних актів, а також щодо поліпшення організації діяльності суду і прокуратури у цій сфері. The work with the complex scientific research of the problems of judicial system, judicial proceedings and acting of the public prosecutor’s office with guaranteeing the legitimateness of the acts of executive bodies and of local government. In this work there have been researched the questions of the legal nature of these acts, the peculiarities of the acts of the executive authority and bodies of local government, guaranteeing the legality by their issue; there are given opinions about the ways of development of the administrative justice in Ukraine and the increasing of its role in an implementation of the control in the rule-making and human rights activity of authority bodies; the role of the public prosecutor’s office in protection of the rights and liberties by means of realization of the control of the legality of acts of the bodies of executive authority and bodies of local government, the interest intermediation of citizens and juridical persons in the court. There have been offered suggestions about the alteration and additions to the laws of Ukraine «About the public prosecutor's office», «About the Local State Administrations», «About the Local Government in Ukraine», «About the Judicial System in Ukraine «, Code of Administrative Legal Proceedings of Ukraine and other statutory acts as well as the improvement of the organization of the court activity and the activity of the public prosecutor's office in this sphere.
The role of the court and the public prosecutor's office in guaranteeing the legitimateness of the acts of executive bodies and of local government
Keywords: правові акти; акти державних адміністрацій; акти місцевого самоврядування; адміністративний суд; судовий контроль; прокуратура; прокурорський нагляд; представництво прокуратурою інтересів громадян в суді; act; acts of State administration; acts of local government; administrative court; judicial control; public prosecutor's office; public prosecutor's (legality) oversight; the interest intermediation of citizens by the public prosecutor's office in the court